Identifying Critical Evidence Gaps in Wound Closure and Incision Management After Total Hip Arthroplasty: Delphi Panel Insights - Margaret H. Ainslie-Garcia, MSc; Lucas A. Anderson, MD; Benjamin V. Bloch, BSc, FRCS; Tim N. Board, FRCS; Antonia F. Chen, MD; Samantha Craigie, MSc; Walter Danker, III, PhD; Najmuddin Gunja, PhD; James Harty, MD; Victor H. Hernandez, MD, MS; Kate Lebedeva, MSc; Mitchell K. Ng, MD; et al. (Arthroplasty Today, 2025)
Background: In total hip arthroplasty (THA), proper management of surgical incisions is essential for optimal wound healing and patient outcomes. Despite advances in surgical techniques, significant challenges remain in preventing complications and infections. This study aimed to identify evidence gaps in THA wound care, including presurgical preparation, intraoperative practices, and postsurgical complications. Methods: Using a modified Delphi method, 20 expert orthopedic surgeons from Europe and North America participated in a 3-phase consensus process from April 1 to September 30, 2023. This included a preliminary questionnaire, a remote conference, and a final online survey. The panel reviewed literature and achieved agreement on 18 consensus statements regarding wound care in THA. A secondary aim was to identify critical gaps in current wound care knowledge. Results: Consensus was reached on 18 statements. Key gaps were identified in the effectiveness of mesh-adhesive dressings, optimal closure methods (skin adhesives, staples, sutures), cost benefit of barbed sutures, and appropriate use of negative pressure wound therapy. These findings highlight the need for further research to validate best practices and guide standardized evidence-based protocols. Conclusions: Addressing these evidence gaps is essential to improve THA wound care methods. Future studies should compare closure techniques and new technologies to develop more efficient patient-centered strategies. Bridging these gaps may reduce complications, enhance outcomes, and lower the burden of wound-related issues in THA.